Model Pendidikan Akhlak Bagi Anak Dalam Keluarga Kyai - Munasir (KAMALIYAH : Jurnal Pendidikan Agama Islam, 2023)
The study "Moral Education Model for Children in Moslem Clerics' Families" investigates how Moslem clerics in Rancahilir Village, Pamanukan District, Subang educate their children morally. It addresses the concern that Indonesian youths lack religious and noble values. Employing a natural qualitative approach with a descriptive method, the research focuses on ongoing societal issues, particularly moral education in Moslem clerics' families. Three Moslem clerics (AJ, AK, and ZA) serve as primary sources. Data collection methods include observation, structured interviews, and document analysis, validated through member-check and triangulation. Findings reveal a clear moral education concept and objective aimed at fostering religious, knowledgeable, and pious character development in children. Methods vary according to age group, emphasizing customs, role models, guidance, and appropriate disciplinary actions.